2020
DOI: 10.7196/samj.2020.v110i11.14828
|View full text |Cite
|
Sign up to set email alerts
|

Let’s get physical: A prospective pedometer study of doctors working in a South African emergency department

Abstract: Physical inactivity has been referred to as a pandemic and is the fourth leading contributing cause of mortality worldwide. [1] The positive impact of physical activity on health is well known, and lack thereof is known to increase the risk of several non-communicable diseases such as hypertension, coronary artery disease and type 2 diabetes. [1,2] This increased risk has local significance, as South Africans have been found to be among the least active people on the African continent. [3] South Africans' phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In this study, participants averaged only 360 SPH during morning clinic sessions. A review of the literature suggested that this step number was the lowest among all medical disciplines that have been evaluated similarly; cardiologists, cardiothoracic surgeons, anesthesiologists, emergency physicians, internists, and others, averaged between 430 and 744 SPH in previous pedometer-based studies (Abd et al, 2012; Atkinson et al, 2005; Beringer et al, 2020; Conzett-Baumann et al, 2009; Cuthill et al, 2008; Peters et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, participants averaged only 360 SPH during morning clinic sessions. A review of the literature suggested that this step number was the lowest among all medical disciplines that have been evaluated similarly; cardiologists, cardiothoracic surgeons, anesthesiologists, emergency physicians, internists, and others, averaged between 430 and 744 SPH in previous pedometer-based studies (Abd et al, 2012; Atkinson et al, 2005; Beringer et al, 2020; Conzett-Baumann et al, 2009; Cuthill et al, 2008; Peters et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that this recommendation is fairly equivalent to the contemporary goal of 10,000 daily steps (Tudor-Locke & Bassett, 2004). Although physicians are more likely to achieve the above fitness goals than the general population (Stanford et al, 2012), workplace-associated limitations present a significant challenge toward reaching recommended levels of daily PA, even in relatively “active” specialties (Beringer et al, 2020; Williams et al, 2015). Based on reviews done by the authors, this study is the first to document pedometer-measured PA levels among ophthalmologists in the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For shift workers, lack of time and work-related fatigue may explain workers’ low levels of physical activity [ 20 ]. According to a study conducted in shift working South African doctors, more steps were reported when working longer shifts, thus resulting in more physical activity at work [ 21 ]. The factors influencing the implementation and effectiveness of health promotion programs in both shift and regular day workers need to be understood to improve workers’ health.…”
Section: Introductionmentioning
confidence: 99%